Autismo e família: revisão bibliográfica em bases de dados nacionais - Hamer, Bruna Laselva [UNESP]; Manente, Milena Valelongo [UNESP]; Capellini, Vera Lúcia Messias Fialho [UNESP] (My University, 2014)
Early studies involving childhood autism attributed to family involvement in impairment of psycho-emotional development of the child. The purpose of this study was to review the literature related to autism and family in two national databases (Theses Database of Capes and Scientific Electronic Library Online) without defining a specific period as well as identify the main thematic focused. Were located 29 studies in Theses Database of Capes, the first record in 1990 and 12 in Scientific Electronic Library Online, the first publication in 2001. The results were grouped into seven categories. The categories “Quality of Life” and “Family Relations” concentrate most of publications on Theses Database. Already in Scientific Electronic Library Online, mostly refers to the “Family Relations” and “literature review”. It was found that none of theses or dissertations was published in scientific paper format, hampering the dissemination of research in the area.

Os primeiros estudos envolvendo o autismo infantil atribuíam à família participação no comprometimento do desenvolvimento psicoafetivo da criança. A proposta deste estudo foi revisar a literatura relacionada ao autismo e família em duas bases de dados nacionais (Banco de Teses e Dissertações da Capes e Scientific Electronic Library Online), sem delimitação de período específico, bem como identificar as principais temáticas focadas. Foram localizados 29 estudos no Banco de Teses e Dissertações da Capes, sendo o primeiro registro em 1990 e 12 na Scientific Electronic Library Online, sendo a primeira publicação de 2001. Os resultados foram agrupados em sete categorias. As categorias “Qualidade de vida” e “Relações familiares” concentram a maioria das publicações no Banco de Teses e Dissertações da Capes. Já na Scientific Electronic Library, a maioria refere-se as “Relações familiares” e “Revisão bibliográfica”. Identificou-se que nenhuma das teses ou dissertações foi publicada em formato de artigo científico, prejudicando a divulgação das pesquisas na área.
Family and autism: literature review in national databases
Keywords: Autism; Family; Child development; Literature revision; Global development derangement; Autismo; Família; Desenvolvimento infantil; Revisão de literatura; Transtorno global do desenvolvimento